Coronary Sparing Aneurysmectomy - Radner, Caroline; Hagl, Christian; Juchem, Gerd; Dashkevich, Alexey (The Thoracic and Cardiovascular Surgeon Reports, 2023)
Repairing left ventricular aneurysms that form after myocardial infarction may be challenging, especially if located close to the important native coronary arteries. Here, we describe a rare case of anterolateral aneurysm of the basal LV wall and a safe, efficient approach for a patch plasty sparing the native left anterior descending.
Keywords: aneurysm; coronary artery bypass grafts surgery; myocardial infarction